2020
DOI: 10.3390/educsci10040106
|View full text |Cite
|
Sign up to set email alerts
|

Student Participation in Online Content-Related Discussion and Its Relation to Students’ Background Knowledge

Abstract: This paper presents two novel network methods developed for education research. These methods were used to investigate online discussions and the structure of students’ background knowledge in a blended university course for pre-service teachers (n = 11). Consequently, these measures were used for correlation analysis. The social network analysis of the online discussions was based on network roles defined using triadic motifs instead of more commonly used centrality measures. The network analysis of the backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This type of complex understanding might be especially difficult for young learners and learners who have not had appropriate coregulation experiences with parents or other caregivers prior to coming to school (Hadwin et al, 2016). Also, as learners are exposed to complex content, differences in background knowledge and prior experience lend themselves to differential abilities to participate in online courses without carefully structured materials and activities (Turkkila and Lommi, 2020).…”
Section: Cognition and Structured Learningmentioning
confidence: 99%
“…This type of complex understanding might be especially difficult for young learners and learners who have not had appropriate coregulation experiences with parents or other caregivers prior to coming to school (Hadwin et al, 2016). Also, as learners are exposed to complex content, differences in background knowledge and prior experience lend themselves to differential abilities to participate in online courses without carefully structured materials and activities (Turkkila and Lommi, 2020).…”
Section: Cognition and Structured Learningmentioning
confidence: 99%
“…Previous studies conducted before and during the COVID-19 have shown that students from underserved backgrounds (e.g., such as culturally and linguistically minority students, students with low socioeconomic status, students living in rural areas, and first-generation to higher education students) encountered multiple structural and socio-cultural challenges related to distance learning. These difficulties included the lack of access to technological resources ( 5 ), limited time and space ( 6 ), disconnection from faculty members and peers ( 7 ), lack of culturally relevant pedagogies ( 8 , 9 ), and difficulties in adjusting to self-directed learning ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…These connections can be constructed from social media, questionnaires or otherwise reported relationships or interactions. For example, SNA has been used to study online written communications (e.g., Martínez, Dimitriadis, Rubia, Gómez, & De la Fuente, 2003;Turkkila & Lommi, 2020) and classroom interactions. These interactions have been defined differently, but usually they are connected to student discourse.…”
Section: Network Analysis In Science Education Researchmentioning
confidence: 99%